Tuvan language in legal and functional aspect - Borgoiakova, Tamara G.; Bitkeeva, Aysa N. (The New Research of Tuva, 2020)
The article examines both positive and negative aspects of the language policy in the Republic of Tuva. Although Tuvan language still preserves its high demographic power and the status of a state language of one of the Russia’s constituent republics, the younger generation of Tuvans keeps suffering from a linguistic shift. The language is functionally weakening its position both as the state language of a region and as the first language of its titular ethnicity.At present, slightly over 50% respondents from among Tuvans aged 18-30 are fluent in their native tongue, and over 70% of these speak Tuvan with their children. In the capital of the republic, only 62% of Tuvan schoolchildren study their native language. As a result, active Russian-Tuvan bilingualism is not universal among Tuvan children, while the number of those speaking only Russian keeps increasing. At the same time, in the countryside there are children who know little or almost no Russian. What is perceived as a contradiction between the positive attitude to the native language among Tuvans and the choice of Russian as the language of school education and even of family communication. This is due to the insufficiency or inaccessibility of information on the benefits of bilingualism and on the importance of one’s native language for children’s intellectual and emotional development, as well as their psychological stability.An important positive factor of Tuva’s language policy is the start of a dialogue between its two major actors – the authorities and language activists. Under the State Development program of supporting Tuvan language, 2017-2020, language protection will receive financial aid, and the implementation of the program will be publicly discussed. This implies an opportunity to reverse the language shift and build up a balanced Tuvan-Russian and Russian-Tuvan bilingualism while preserving the existing interethnic consensus in the Republic of Tuva.
Keywords: language policy; Tuvan language; Tuva; mother tongue; active bilingualism; language loyalty; language shift; public debate